Non-descent vaginal hysterectomy for large uterus-safety and feasibility - R., Rameshkumar; Naik, Sahana N.; ., Dhanalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Non Descent Vaginal Hysterectomy (NDVH) is removal of uterus through vagina in non-prolapsed uterus. The objective of the present study was to assess safety and feasibility of NDVH in patients with large uterus (>12 weeks size uterus). Methods: Retrospective study was conducted in Department of Obstetrics and Gynecology of Shree Dharmasthala Manjunatheshwara (SDM) College of Medical Sciences and Hospital, Dharwad, India from May2014 to May 2017. Effort was made to perform hysterectomies vaginally in women with benign conditions with large uterine size. Information regarding age, parity, uterine size, blood loss, duration of operation, number of fibroids, other surgical difficulties encountered, intra–operative and post-operative complications were recorded. Results: Total of 65 cases was selected for NDVH with large uterine size. All successfully underwent NDVH. 25 patients had uterus of 10-12 weeks size, 17 had uterine size of 12-14 weeks size. Mean duration of surgery was 90 min. Mean blood loss was 300ml. Post-operative complications were minimal. All patients had early mobility with faster resumption to daily activities. Mean hospital stay was 4-5 days. Conclusions: Non descent vaginal hysterectomy is safe, cost effective method of hysterectomy in women with large uterus requiring hysterectomy for benign conditions with less complications, shorter hospital stay and less morbidity.